Dissimilar metal joining of aluminium and magnesium alloy by gas metal arc spot welding technique - Ishak, M.; Idris, Siti Rabiatull Aisha; Aiman, M. H.; Yusoff, Wan Azhar (2017)
Innovative welding technique for joining aluminum and magnesium alloys in automobile, aviation, aerospace and marine industries would achieve weight reduction, high specific strength as well as increase fuel efficiency and reduce environmental pollution. Friction stir welding (FSW) is capable of joining magnesium alloys without melting, and thus, it can eliminate problems related to solidification. Thin sheet AZ31B finds its application in automotive, aviation and also electronic devices parts such as computer casing and thin plate part in smartphone. In joining thin sheet AZ31B, laser welding is promising the best joining method compared to arc and solid state welding in producing small weldments.Magnesium alloy AZ31 was successfully welded by using friction stir welding. Shoulder to pin diameter ratio give effect to the mechanical properties and microstructural properties of AZ31 FSW. The optimum shoulder to pin ratio shows higher tensile strength with fine and equiaxed grain size that indicate higher hardness.The fine grain produced higher hardness values compared to the coarser grain with a value of 77 Hv for the optimized sample. Optimized sample has 80.5 MPa of tensile shear strength and fracture load of 800 N which could be applied in replacing Al and steel especially for the electronic parts since the strength was acceptable for a thin product. However, poor mechanical properties of welding joint between aluminum and magnesium alloys due to the formation of AlmMgn type brittle intermetallic compounds is the main barrier for extensive uses of these two alloys especially in transportation sectors.The results revealed that more significant mechanical properties were achieved with stainless steel filler compared to aluminum filler. The maximum yield strength, ultimate tensile strength and fracture toughness were 203.09 MPa, 249.33 MPa and 27.49 MPa√m respectively with steel filler; and 176.30 MPa, 226.28 MPa and 20.22 MPa√m respectively with aluminum filler.The output of this research exhibited very significant mechanical properties of the joint that can facilitate the extensive uses of A7075-T651 and AZ31B alloys in mass production of light weight vehicle structures in transportation industries.